2005
DOI: 10.1007/s11103-005-0953-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis by cDNA-AFLP highlights a set of new signaling networks and translational control during seed dormancy breaking in Nicotiana plumbaginifolia

Abstract: Seed dormancy in Nicotiana plumbaginifolia is characterized by an abscisic acid accumulation linked to a pronounced germination delay. Dormancy can be released by 1 year after-ripening treatment. Using a cDNA-amplified fragment length polymorphism (cDNA-AFLP) approach we compared the gene expression patterns of dormant and after-ripened seeds, air-dry or during one day imbibition and analyzed 15,000 cDNA fragments. Among them 1020 were found to be differentially regulated by dormancy. Of 412 sequenced cDNA fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 80 publications
8
86
0
3
Order By: Relevance
“…As for proteome oxidation, it is worth to note that the effects of MV and cyanide on gene expression share some homology, highlighting again that their mechanisms of action are probably very close, involving ROS signaling. We also observed that 11 out of 78 TDF were found in nondormant seeds after after-ripening (data not shown) showing that changes in gene expression may occur in the dry state, as already suggested by Leubner-Metzer, 17 Bove et al 13 and Leymarie et al 15…”
Section: Is the Proteome The Only Target Of Ros In Seed Dormancy Allesupporting
confidence: 80%
See 1 more Smart Citation
“…As for proteome oxidation, it is worth to note that the effects of MV and cyanide on gene expression share some homology, highlighting again that their mechanisms of action are probably very close, involving ROS signaling. We also observed that 11 out of 78 TDF were found in nondormant seeds after after-ripening (data not shown) showing that changes in gene expression may occur in the dry state, as already suggested by Leubner-Metzer, 17 Bove et al 13 and Leymarie et al 15…”
Section: Is the Proteome The Only Target Of Ros In Seed Dormancy Allesupporting
confidence: 80%
“…[13][14][15] Although we propose ROS production and proteome oxidation as a key regulatory mechanism in the breaking of dormancy, we consider that the regulation of this phenomenon is multifactorial and requires a coordinated activation of various Hydrogen peroxide content and CATA1 gene expression in axes isolated from dormant and non-dormant sunflower seeds before imbibition (dry) or after 8 and 16 h of imbibition on water at 10°C.. Values are means of five replicates ± SD (H2O2).…”
Section: Is the Proteome The Only Target Of Ros In Seed Dormancy Allementioning
confidence: 99%
“…In tobacco seeds, the proportion of genes repressed or induced during dormancy maintenance does not appear to differ significantly in the general categories of primary metabolism, cellular communication/signaling, and transcriptional control (Bove and others 2005). Indeed, within dormant seeds, the upregulated genes belong to the general categories of cell rescue, secondary metabolism, and transport facilitation.…”
Section: Maintenance Of Dormancy At Seed Maturitymentioning
confidence: 92%
“…Interestingly, upon dormancy termination, virtually all of the upregulated genes belong to the functional categories of cellular organization, regulated proteolysis (for example, photomorphogenesis repressor-like proteins of light signaling), and translational control. Thus, light perception, components of signaling networks, translational control, and regulated proteolysis are all linked to the maintenance of dormancy and its termination (Bove and others 2005).…”
Section: Maintenance Of Dormancy At Seed Maturitymentioning
confidence: 99%
See 1 more Smart Citation